Drogová scéna v České republice se zaměřením na region východních Čech - Veselá, Jana (Univerzita Pardubice, 2001)
Drugs are one of the most weighty social and healthy problem ofpart of the growing up population in Czech Republic in present days. This reality tend state and public institutions to creation of projects and programs, what would be pointed against arranged sale of drugs and created uses provision for reduce demand and offer for drugs.
Keywords: Drogy; prevence; sociálně patologické jevy; protidrogová politika; východní Čechy